Multifunctional chemical sensors and luminescent thermometers based on lanthanide metal–organic framework materials. Issue 15 (21st March 2016) - Wang, Kai-Min; Du, Lin; Ma, Yu-Lu; Zhao, Jing-Song; Wang, Quan; Yan, Tong; Zhao, Qi-Hua
Abstract : We report six new uncommon isostructural 3D lanthanide-MOF materials which are the first examples of a multifunctional luminescent sensor for quantitatively detecting the temperature (10–300 K) and the concentration of Pb 2+ and Fe 3+ ions in ethanol solution. Abstract : Six new highly symmetrical and isostructural 3D lanthanide metal–organic frameworks (Ln-MOFs) [Ln2 (Ccbp)3 ·6H2 O]·3Cl − ·4H2 O Ln = Tb (1 ), Eu (2 ), Gd (3 ), Sm (4 ), Er (5 ) and Yb (6 ), Ccbp − = 4-carboxy-1-(4-carboxybenzyl)pyridinium, and the mixed Ln-MOF [Tb1.828 Eu0.172 (Ccbp)3 ·6H2 O]·3Cl − ·4H2 O (7 ) have been successfully synthesized and fully characterized. The complex1 was utilized as a representative chemosensor to detect small molecules, cations and anions, respectively. Interestingly, 1 exhibited dual-functional detection of Pb 2+ and Fe 3+ ions in ethanol with excellent linear variation to quantify the corresponding concentration change. In addition, the temperature-dependent luminescence properties of1, 2 and7 have also been investigated systematically, which demonstrated that both1 and7 have potential to quantitatively detect temperature as a luminescent thermometer over a wide range from 10–300 K for1 and 10–170 K for7 . Thus, the as-obtained Ln-MOF materials have potential to serve as the first examples of a multifunctional luminescent sensor for quantitatively detecting the temperature (10–300 K) and the concentration of Pb 2+ and Fe 3+ ions in ethanol solution.